A Synthetic Approach to Pyrazolopyranopyrimidinones and Pyrazolopyranooxazinones as Antimicrobial Agents - A. K. Elziaty; G. Bassioni; A. M. A. Hassan; H. A. Derbala; M. S. Abdel-Aziz (Journal of Chemistry)
The hitherto unknown 6-amino-4-(2-chloro-5-nitrophenyl)-3-methyl-1,4-dihydropyrano[2,3-c] pyrazole-5-carbonitrile 1a was synthesized. Both 1a and its 2,4 dichlorophenyl derivative 1b were utilized as building blocks for the preparation of novel class of pyrazolopyrano-[oxazines 2a–d and pyrimidinones 3a–d]. Synthesis of these compounds was achieved by two alternative acylation steps followed by ammonolysis. The structures of the synthesized compounds were elucidated by spectral data and elemental analysis. Screening and evaluation of these products as antimicrobial agents showed that the derivatives 1b, 2s, 3b, and 3d possess a potent activity.